2004
DOI: 10.4049/jimmunol.173.5.3051
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of pDC-Like Cells in Normal Mouse Skin and Melanomas Treated with Imiquimod

Abstract: Among the different subsets of dendritic cells (DC) described in humans and mice, epidermal Langerhans cells and dermal DCs represent the only DC populations resident in normal skin. In this study we describe a population of CD4+CD3− plasmacytoid DC (pDC)-like cells that accumulate in the dermis and spleens of mice topically treated with imiquimod, a low m.w. immune response modifier with potent antiviral and antitumor activities. These CD4+CD3− cells coexpress GR-1, B220, MHC class II, and, to a lesser extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
162
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 60 publications
7
162
0
Order By: Relevance
“…So, in contrast to mDCs and pDCs, Langerhans cells retain an immature phenotype after treatment with imidazoquinolines, although they also become functionally mature. Apart from migration of Langerhans cells from the skin to the lymph nodes, it was also observed that topical treatment with imiquimod resulted in the recruitment of pDCs and activated DCs to the skin [46,53,54]. Moreover, the immune activation observed was related to the number of pDCs recruited to the treatment site [53].…”
Section: Dcs and B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, in contrast to mDCs and pDCs, Langerhans cells retain an immature phenotype after treatment with imidazoquinolines, although they also become functionally mature. Apart from migration of Langerhans cells from the skin to the lymph nodes, it was also observed that topical treatment with imiquimod resulted in the recruitment of pDCs and activated DCs to the skin [46,53,54]. Moreover, the immune activation observed was related to the number of pDCs recruited to the treatment site [53].…”
Section: Dcs and B Cellsmentioning
confidence: 99%
“…The induced cytokines and chemokines play an important role in the effects of TLR7/8 agonists as described above. In the previous studies in which imiquimod was applied topically, this IRM led to local cytokine production, thereby altering the tumor microenvironment with a Th1-polarizing cytokine pattern that promotes effective antitumor immune responses [46,83,84]. Cytokines induced by TLR7/8 agonists also have additional functions, embedded in the complex process of immune activation, such as rendering CD4 ϩ effector T cells refractory to Treg cell-mediated suppression [68,85].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…The major clinical limitations of many TLR agonists are the risk of dose-limiting toxicities associated with their systemic delivery (10-12) and metastasis stimulation (13-15). Furthermore, some previously investigated TLR agonists are restricted to injection directly into tumor tissue (3,(16)(17)(18), an approach that will likely have limited therapeutic value in cancer patients with metastatic disease.TLR5 is unique among TLRs as a potential target for systemic anticancer immunotherapy. Studies have shown that the only known natural TLR5 agonist, flagellin, flagellin-expressing Salmonella bacteria, and a pharmacologically optimized flagellin derivative named entolimod (CBLB502) have antitumor effects in several tumor models (19-23), including mouse models of liver metastases (24-26).…”
mentioning
confidence: 99%
“…The major clinical limitations of many TLR agonists are the risk of dose-limiting toxicities associated with their systemic delivery (10)(11)(12) and metastasis stimulation (13)(14)(15). Furthermore, some previously investigated TLR agonists are restricted to injection directly into tumor tissue (3,(16)(17)(18), an approach that will likely have limited therapeutic value in cancer patients with metastatic disease.…”
mentioning
confidence: 99%
“…7,8 Indeed, the presence of DCs in human carcinomas has been largely documented 9 and certain studies associated the quality and/or quantity of tumor-infiltrating DCs to a favorable prognosis for the patient. [10][11][12][13] It is traditionally believed that apoptotic bodies or necrotic debris are generated as a result of direct killing of tumor cells by NK cells and CTLs. 1 However, there is growing evidence that conventional DCs or certain DC subsets are endowed with a direct tumoricidal property by delivering cell death signals to pre-malignant/malignant cells, and also by providing signals required for their own maturation into immunostimulatory APCs.…”
mentioning
confidence: 99%